Computerized tomographic prediction of flexor tendon injuries complicating hamate hook fractures. (May 2019) - Takeda, Shinsuke; Tatebe, Masahiro; Ishii, Hisao; Morita, Akimasa; Wakai, Kenji; Hirata, Hitoshi
We reviewed computerized axial tomography of 28 patients with hamate hook fractures who had surgical resection of the hook. We analysed the relationship between the fragment height ratio, fragment gap, and intraoperative findings of the tendons. We determined whether parameters in the images can predict complication of tear or disruption of the flexor tendons to the ring or little fingers. Of 28 patients, 16 had fragment height ratios between 50–74; ten among them had worn (eight patients) or ruptured (two patients) flexor tendons. Nine of the ten patients had fragment gaps greater than 2 mm. The remaining 12 patients had fragment height ratios between 75–100 and had intact tendons. We conclude that a fragment height ratio greater than 75 and fragment gap less than 2 mm in computer tomography may rule out tear or disruption of the flexor tendons of the ring and little fingers after hamate hook fractures, and a fragment height ratio between 50–74 with fragment gap greater than 2 mm indicates a high risk of flexor tendon tear or disruption. Level of evidence : IV